2014
DOI: 10.1097/bsd.0b013e31825bfb69
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Study to Evaluate the Effect of PMMA Augmentation and Restoration of the Strength of Cervical Vertebral Screws Inserted in an Osteoporotic Vertebral Body

Abstract: The results indicated that both PMMA augmentation and PMMA restoration could significantly increase cervical screw pull-out strength and antifatigue capability. The results provide a biomechanical justification for spine surgeons to use PMMA for augmentation or restoration in cases of surgeries with poor bone quality or osteoporotic vertebral bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Our previous research has shown that this rate is appropriate to avoid damage to the vertebrae by preventing sudden pullout of the screw 21 . Failure was defined as the point at which there was a precipitous drop in the load-displacement curve.…”
Section: Test Groupsmentioning
confidence: 99%
“…Our previous research has shown that this rate is appropriate to avoid damage to the vertebrae by preventing sudden pullout of the screw 21 . Failure was defined as the point at which there was a precipitous drop in the load-displacement curve.…”
Section: Test Groupsmentioning
confidence: 99%
“…At the level of C2, pedicle fixation has been shown to have twice the pullout over pars fixation. 13 In the subaxial spine, pedicle screws have been utilized from an anterior 2 - 28 or posterior approach. 13 , 18 - 21 While they place the vertebral artery and nerve root at increased risk, cervical pedicle screws allow for improved biomechanical strength.…”
Section: Resultsmentioning
confidence: 99%
“…PMMA augmentation has been described in the setting of anterior vertebral body screws [25][26][27][28][29][30][31][32] and odontoid fixation of the elderly. [29][30][31] Augmentation may occur prior to screw placement (cement-first technique) by injecting PMMA through a tapped screw hole or after screw placement (in situ technique) whereby cement is injected through a cannulated and fenestrated screw design.…”
Section: Screw Augmentationmentioning
confidence: 99%
See 2 more Smart Citations